Strategic Consulting Tools and methods for successful strategy missions - Chereau, Philippe (Springer International Publishing, 2018)
Whether you are a business leader, internal business partner or external consultant, there are six key strategy missions that you will need to undertake as you deal with the re-positioning and growth issues that all businesses face at one stage or another during their life-cycle: assessing the environment defining a strategic positioning choosing a growth strategy expanding internationally combining strategy, and innovation or (re)designing the business model Meschi and Chereau bridge the gaps between academic theory and real world practice, between strategic analysis and strategic management, and between planning and doing, by providing you with six essential mission briefings to help you deliver the best possible outcome. Each briefing is structured the same way, beginning with an outline of the consulting mission and its content before examining the theoretical background, before setting out a complete and practical methodology to complete the mission along with all the tools you will need along the way.